2018
DOI: 10.1080/10717544.2017.1419513
|View full text |Cite
|
Sign up to set email alerts
|

Improved intestinal absorption of paclitaxel by mixed micelles self-assembled from vitamin E succinate-based amphiphilic polymers and their transcellular transport mechanism and intracellular trafficking routes

Abstract: To ensure that antitumor drugs can be effectively transported across intestinal barrier and then quickly released in tumor cells, mixed polymeric micelles (Mix-PMs) were designed and fabricated by combining poly(2-ethyl-2-oxazoline)-vitamin E succinate (PEOz-VES) with TPGS1000 for enhancing intestinal absorption of paclitaxel. PEOz-VES exhibited an extremely low critical micelle concentration and negligible cytotoxicity. The Mix-PMs were characterized to have about 20 nm in diameter, uniform spherical morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 54 publications
2
48
0
Order By: Relevance
“…Park et al [41] reported that surfactants with permeability-enhancing effects and a medium fatty acid chain length may penetrate the lipid bilayer easily because of their proper lipid solubility. Qu et al [42] reported the enhanced permeability of paclitaxel in Caco-2 cells using paclitaxel-loaded mixed polymeric micelles combining poly (2-ethyl-2-oxazoline)-vitamin E succinate with TPGS, in which the energy-dependent transmembrane transport of a mixed micelle formulation was involved via both clathrin-and caveolae-mediated micropinocytosis mechanisms. Taken together, a mixed micelle formulation consisting of a large mw surfactant could penetrate the intestinal lumen through its decreased cell integrity, which was evidenced by the decrease in the TEER values and/or micropinocytosis transmembrane mechanisms [27,39,42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Park et al [41] reported that surfactants with permeability-enhancing effects and a medium fatty acid chain length may penetrate the lipid bilayer easily because of their proper lipid solubility. Qu et al [42] reported the enhanced permeability of paclitaxel in Caco-2 cells using paclitaxel-loaded mixed polymeric micelles combining poly (2-ethyl-2-oxazoline)-vitamin E succinate with TPGS, in which the energy-dependent transmembrane transport of a mixed micelle formulation was involved via both clathrin-and caveolae-mediated micropinocytosis mechanisms. Taken together, a mixed micelle formulation consisting of a large mw surfactant could penetrate the intestinal lumen through its decreased cell integrity, which was evidenced by the decrease in the TEER values and/or micropinocytosis transmembrane mechanisms [27,39,42].…”
Section: Discussionmentioning
confidence: 99%
“…Qu et al [42] reported the enhanced permeability of paclitaxel in Caco-2 cells using paclitaxel-loaded mixed polymeric micelles combining poly (2-ethyl-2-oxazoline)-vitamin E succinate with TPGS, in which the energy-dependent transmembrane transport of a mixed micelle formulation was involved via both clathrin-and caveolae-mediated micropinocytosis mechanisms. Taken together, a mixed micelle formulation consisting of a large mw surfactant could penetrate the intestinal lumen through its decreased cell integrity, which was evidenced by the decrease in the TEER values and/or micropinocytosis transmembrane mechanisms [27,39,42]. Our berberine-loaded mixed micelle formulation could act as a P-gp modulator and CYP inhibitor in the enterocytes through the decreased cell membrane integrity by increasing the modulation of tight junctions in parts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis and behaviour of amphiphiles in solution has been the focus of numerous experimental [1][2][3][4] and theoretical [5][6][7] studies over the past few decades. Self-assembly, exemplified in nature with molecules such as phospholipids, cholesterol, or bile acids, occurs in order to reduce the overall free energy of a system by minimising interactions between water and hydrophobic moieties, 8 resulting in the formation of supramolecular structures of varying morphologies, such as spherical micelles, 9,10 worm-like micelles, 11 and vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…Oral administration has been considered as a preferred route in clinical treatment due to its convenience, patient compliance, and lower-cost. Over the decades, enormous developments in nanotechnology have introduced new approaches to improve oral drug delivery (Shan et al., 2016 ; Fan et al., 2018 ; Qu et al., 2018 ). However, the ideal oral delivery efficacy still confronts great challenges, including the poor physicochemical properties of drugs, harsh gastrointestinal environment, the diffusion barrier of intestinal mucus layer, and the compromised enterocyte absorption before entering systemic circulation (Shan et al., 2015 ; Tang et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%